2000
DOI: 10.1071/rd98127
|View full text |Cite
|
Sign up to set email alerts
|

Maternal copper supplementation protects the neonatal rat lung against the adverse effects of maternal nicotine exposure

Abstract: Maternal nicotine exposure interferes with the extracellular formation of the connective tissue framework of the neonatal lung, a process that is dependent on copper-dependent lysyl oxidase. It has been shown that, during the phase of lung development associated with alveolarization, maternal nicotine exposure resulted in a reduction in the copper content and thus conceivably in the activity of lysyl oxidase of the neonatal lung. Therefore the aims of this study were (a) to determine the effects of maternal ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…This is in contrast to the findings of recent research that clearly showed that copper supplementation during gestation and lactation, and thus during all phases of lung development, prevent the induction of microscopic emphysema [36]. This implies that maternal copper supplementation form the end of the saccular phase of lung development in the offspring slowed down the process whereby microscopic emphysema was induced, but was not preventing it.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This is in contrast to the findings of recent research that clearly showed that copper supplementation during gestation and lactation, and thus during all phases of lung development, prevent the induction of microscopic emphysema [36]. This implies that maternal copper supplementation form the end of the saccular phase of lung development in the offspring slowed down the process whereby microscopic emphysema was induced, but was not preventing it.…”
Section: Discussioncontrasting
confidence: 76%
“…It can therefore be expected that a decrease in the copper content of the developing lung will result in a slower lung development or that copper supplementation may enhance lung maturation. In a recent study, we showed that maternal copper supplementation indeed enhanced lung maturation in the offspring [36]. We also showed that maternal nicotine exposure during gestation and lactation resulted in a lower copper content of the lungs of the offspring and a concomitant decrease in the number of alveoli and internal surface area available for gas exchange.…”
Section: Discussionmentioning
confidence: 78%
“…While exposure to nicotine can result in the activation of two major signaling pathways (MAP-kinase and PKC) that are known to inhibit apoptosis, nicotine regulation of MAP and ERK kinase activity is not dependent on PKC. These effects of nicotine occur at concentrations that are generally found in the blood of smokers, and could lead to disruption of the critical balance between cell death and proliferation [58,126]. The inhibition of apoptosis by nicotine may contribute to the slower thinning of the alveolar septa of the lungs of rat pups that were exposed to nicotine during gestation and suckling [127].…”
Section: Nicotine and Cell Signaling: Apoptosis And Lung Developmentmentioning
confidence: 99%
“…Furthermore, it was shown that the nicotine-mediated stimulation of surfactant synthesis was by its direct effect on ATII cells, whereas ATII cell proliferation and metabolism were mediated via its paracrine effects on the adepithelial fibroblasts, permanently altering the “developmental program” of the developing lung. Nicotine’s effects on lung fibroblasts have also been explored in rat and monkey models of perinatal nicotine exposure [67, 7173]. Under in vitro conditions it was shown that nicotine exposure disrupts epithelial-mesenchymal interactions and causes lipofibroblast-to-myofibroblast transdifferentiation [3, 5].…”
Section: Specific Cellular and Molecular Effects Of Nicotine On The Dmentioning
confidence: 99%
“…Therefore, prenatal nicotine exposure seems to alter lung development through multiple pathways, but a clear understanding of the underlying mechanisms involved and the mechanistic link between perinatal nicotine exposure and altered pulmonary structure and function are still not completely understood. Consequently, it is not surprising that there is no effective intervention to prevent the damaging effects of in utero nicotine exposure, though some strategies such as vitamin C and copper supplementation have been suggested as attractive options [70, 73]. However, the safety of these interventions is not established, the mechanisms underlying possible beneficial effects remain poorly understood, and the protection afforded is only partial and inconsistent.…”
Section: Specific Cellular and Molecular Effects Of Nicotine On The Dmentioning
confidence: 99%